Case Report on Perinatal Hepatitis C Virus Transmission from Mother to Child in Najaf, Iraq - Al-Waeli, Alaa (Medical Science Journal for Advance Research, 2024)
Background: The hepatitis C virus causes an inflammation of the liver, known as hepatitis C. The virus can cause both acute and chronic hepatitis, ranging in severity from a mild illness to a serious, lifelong illness including liver cirrhosis and cancer. Case presentation A 32-year-old woman in Najaf, Iraq. The first case of hepatitis C in Najaf is for a woman who transmits the infection to the fetus during pregnancy. She was diagnosed with HCV by doing viral tests before her thyroidectomy in 2016. She was treated with Ledipasvir /sofobuvir (90 mg+400 mg) one dose daily for 12 to 24 weeks because HCV infection can be an opportunistic infection for pregnant women and infected infants. Conclusion: This report presents an unusual case of HCV infection infant transmission from mother, the present case is the first one in Najaf.